2018
DOI: 10.1111/epi.14555
|View full text |Cite|
|
Sign up to set email alerts
|

Progress report on new antiepileptic drugs: A summary of the Fourteenth Eilat Conference on New Antiepileptic Drugs and Devices (EILAT XIV). II. Drugs in more advanced clinical development

Abstract: Summary The Fourteenth Eilat Conference on New Antiepileptic Drugs and Devices (EILAT XIV) took place in Madrid, Spain, on May 13‐16, 2018 and was attended by 168 delegates from 28 countries. The conference provided a forum for professionals involved in basic science, clinical research, regulatory affairs, and clinical care to meet and discuss the latest advances related to discovery and development of drugs and devices aimed at improving the management of people with epilepsy. This progress report provides a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
73
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(74 citation statements)
references
References 69 publications
1
73
0
Order By: Relevance
“…Gregory N. Beatch, 1 Isabella Premoli, 2 Rostam Namdari, 1 Jay A. Cadieux, 1 XEN1101 is an NCE that enhances activation of neuronal Kv7.2-7.5 (KCNQ2-5) potassium channels, which constitute the molecular components of the slow activating/ deactivating voltage-gated M-current. Initially described in the EILAT XIII progress report as 1OP-2198, 7 this second generation Kv7 channel opener is more potent and target-selective than the first generation Kv7 channel modulator retigabine, which has been shown to be clinically effective in the treatment of focal epilepsy.…”
Section: Xen1101mentioning
confidence: 99%
See 1 more Smart Citation
“…Gregory N. Beatch, 1 Isabella Premoli, 2 Rostam Namdari, 1 Jay A. Cadieux, 1 XEN1101 is an NCE that enhances activation of neuronal Kv7.2-7.5 (KCNQ2-5) potassium channels, which constitute the molecular components of the slow activating/ deactivating voltage-gated M-current. Initially described in the EILAT XIII progress report as 1OP-2198, 7 this second generation Kv7 channel opener is more potent and target-selective than the first generation Kv7 channel modulator retigabine, which has been shown to be clinically effective in the treatment of focal epilepsy.…”
Section: Xen1101mentioning
confidence: 99%
“…These include adenosine and adenosine kinase (ADK) inhibitors, BIS‐001 (huperzine A), 2‐deoxy‐ d ‐glucose, FV‐082, FV‐137, JNJ‐40411813, JNJ‐55511118 and analogs, ketone‐enhanced antiepileptic drugs, OV329, oxynytones, TAK‐935 (OV935), XEN901, and XEN1101. Information on potential AEDs in more advanced development is presented in an accompanying article …”
Section: Introductionmentioning
confidence: 99%
“…An ideal drug would have near absolute bioavailability, distribution with low protein binding, and non-CYP mediated metabolism such that elimination would be predictable. In contrast, CBD has limited and variable bioavailability for oral oil formulations (<6%), due to extensive first pass metabolism in the liver (Bialer et al, 2017(Bialer et al, , 2018. It was recently demonstrated that the absorption is increased 4-5fold when ingested with a fat-rich meal (Taylor et al, 2018).…”
Section: Pharmacokinetic Properties Of Cbdmentioning
confidence: 99%
“…Pharmacokinetic interactions with CBD. The pharmacokinetic interactions that have been documented so far are related to metabolism; enzyme inhibition of various CYP and UGT enzymes (Geffrey et al, 2015;Gaston et al, 2017;Bialer et al, 2018;Franco and Perucca, 2019). No interactions regarding protein binding have been identified, however, such interactions are possible based on the high degree of protein binding of CBD as well as other AEDs (valproate, stiripentol).…”
Section: What We Do Not Know?mentioning
confidence: 99%
“…In spite of advanced knowledge about antiepileptic drugs (AEDs) and their application in the treatment of epileptic patients, there are still a number of patients inappropriately treated with these AEDs [1]. Each year, several novel compounds are tested in both preclinical conditions and clinical settings in the hope of discovering the most promising drugs that would be able to suppress seizure activity in epileptic patients [2][3][4]. When the treatment with the first current frontline AED failed, clinicians were obliged to try another AED, fully effective against specific seizure types.…”
Section: Introductionmentioning
confidence: 99%